Criminalising lesbian sexual conducts in Malaysia / Nur Ilmi Syakila Mazalan … [et al.] - Mazalan, Nur Ilmi Syakila; Muhammad Khairi, Siti Maisarah; Mohamad Khairudin, Nor Maiezah; Abdul Khalid, Ahmad Basyir (2014)
The purpose of the research paper is to address the issue of lesbian sexual conducts that has become prevalent in Malaysia nowadays. This research is important since it is aimed to fill in the lacuna in our local law in regulating the lesbian sexual conduct in Malaysia. It is also aimed to reduce the issues of lesbianism in our country. Our main argument is that, since there is no law to regulate the lesbian sexual conducts in our Civil Penal Code (Act 574), the issue such as discrimination will arise since the Syariah law criminalise lesbianism between Muslims women, but no such law exist in our Penal Code to criminalise the issue at hand. This research paper is accomplished by several methods, which consisted of an interview with a Syariah lawyer and a questionnaire that was distributed to 100 students in the Faculty of Law UiTM Shah Alam. From the research itself, we found that people do aware of the existence of lesbianism in the country and most of the respondents to the questionnaire that we had distributed do agree that necessary amendment to the Penal Code should be made to the Penal Code in order to have one civil law to regulate the lesbians sexual conduct. Therefore, the abovementioned argument is supported by the findings of the research itself.